Elevating Voices: Community Partner Perspectives on a Broader Impacts Toolkit - Daniel Grant; Nicole Motzer; Chatanika Stoop; Suzanne Taylor (The University of Alabama, 2024)
This article offers community partner perspectives on the National Science Foundation-funded Broader Impacts (BI) Toolkit, a new digital tool researchers can use to improve the societal relevance of their research. Partners suggest three ways the toolkit could be improved moving forward, underscoring the importance of relationship building to any BI activity.